Gandhi's moral politics
1 online resource (xi, 185 pages)
Keywords: "This volume explores the scope and limits of Mahatma Gandhi's moral politics and its implications for Indian and other freedom movements. It presents a set of enlightening essays based on lectures delivered in memory of the eminent historian B. R. Nanda along with a new introductory essay.With contributions by leading historians and Gandhi scholars, the book provides new perspectives on the limits of Gandhi's moral reasoning, his role in the choice of destination by Indian Muslim refugees, his waning influence over political events, and his predicament amid the violence and turmoil in the years immediately preceding partition. The work brings together wide-ranging insights on Gandhi and revisits his religious views, which were the foundation of his morality in politics; his experience of civil disobedience and its nature, deployment and limits; Satyagraha and non-violence; and his struggle for civil rights. The volume also examines how Gandhi's South African phase contributed to his later ideas on private property and self-sacrifice. This book will be of immense interest to researchers and scholars of modern Indian history, Gandhi studies, political science, peace and conflict studies, South Asian studies; to researchers and scholars of media and journalism; and to the informed general reader."--Provided by publisher.